2012
DOI: 10.1890/12-0318.1
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation alters stream fish community structure in dendritic ecological networks

Abstract: Effects of fragmentation on the ecology of organisms occupying dendritic ecological networks (DENs) have recently been described through both conceptual and mathematical models, but few hypotheses have been tested in complex, real-world ecosystems. Stream fishes provide a model system for assessing effects of fragmentation on the structure of communities occurring within DENs, including how fragmentation alters metacommunity dynamics and biodiversity. A recently developed habitat-availability measure, the "den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
128
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 64 publications
6
128
1
Order By: Relevance
“…Still, we found barrier removals associated with maximum gains in the DCI (caused by removal of small barriers) were also associated with the greatest potential for increasing the distributions of small-bodied pelagophilic or lithopelagophilic guilds because the removal of such barriers would reconnect fragments with low probability of occurrence to fragments that have high probability of occurrence. These findings support previous conclusions that the DCI represents a useful tool for approximating potential responses in functional connectivity based on adjustments in structural connectivity (Bourne et al 2011, Perkin and Gido 2012, Perkin et al 2013a.…”
Section: Figsupporting
confidence: 90%
See 2 more Smart Citations
“…Still, we found barrier removals associated with maximum gains in the DCI (caused by removal of small barriers) were also associated with the greatest potential for increasing the distributions of small-bodied pelagophilic or lithopelagophilic guilds because the removal of such barriers would reconnect fragments with low probability of occurrence to fragments that have high probability of occurrence. These findings support previous conclusions that the DCI represents a useful tool for approximating potential responses in functional connectivity based on adjustments in structural connectivity (Bourne et al 2011, Perkin and Gido 2012, Perkin et al 2013a.…”
Section: Figsupporting
confidence: 90%
“…8 This measure incorporates mainstem and tributary habitats of stream networks occurring between barriers and constitutes an informative measure of fish habitat availability (Cote et al 2009, Perkin andGido 2012). To summarize broad-scale patterns in fragmentation, we constructed frequency histograms of fragment network lengths for each basin.…”
Section: Patterns Of Stream Fragmentation and Desiccationmentioning
confidence: 99%
See 1 more Smart Citation
“…If anthropogenic fragmentation is severe, biotic interactions may have little impact on diversity. In an assessment of streams in Kansas, USA, segment fragmentation by roads yielded lower alpha fish species diversity and higher beta fish species diversity compared with segments maintaining high connectivity, regardless of hydrologic stability [115].…”
Section: Barriers To Dispersal and Movementmentioning
confidence: 99%
“…In an elongated river basin, CzeglĂŠdi et al (2016) showed that spatial position of parallel tributaries along the river influenced community structure in the tributaries. Another example of dispersal effects comes from Perkin and Gido (2012) who proved that fragmentation of stream segments by road crossing caused significant changes in fish community structure. Isolated (i.e., fragmented) stream segments had reduced alpha diversity and increased beta diversity (greater dissimilarity) compared to communities that maintained connectivity with relatively natural (unfragmented) segments of the stream network.…”
Section: Patterns In Diversitymentioning
confidence: 99%